Applied of Information Gain Algorithm for Culinary Recommendation System in Lhokseumawe - Rozzi Kesuma Dinata; Novia Hasdyna; Muhammad Alif (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2021)
Information gain is an algorithm that can be used to rank datasets. This research applied the information gain algorithm to the culinary recommendation system in Lhokseumawe city.  Lhokseumawe is one of the tourist destinations in the northen region of  Aceh, due to its strategic location near the beach.  Apart from the beach, culinary is the main choice of tourists when visiting Lhokseumawe city.  The purpose of implementing this recommendation system is to make it easier for tourists to find the best culinary recommendations in Lhokseumawe city based on the value of the data ranking with the information gain algorithm.  The results of this research shown that the highest rank of information gain values is 0.545715, 0.530769, and 0.497328, continuously.  This value provided in the culinary recommendation system in Lhokseumawe city, namely Mie Ayah, Bakso Pim, and Bakso Pak De.